2013
DOI: 10.1051/medsci/20132912017
|View full text |Cite
|
Sign up to set email alerts
|

Rôle de la thrombospondine-1 dans le développement des maladies rénales

Abstract: > La thrombospondine-1 (TSP-1) est une glycoprotéine matricielle de 450 kDa qui possède des propriétés anti-angiogéniques, pro-apoptotiques et immunomodulatrices. Il s'agit aussi d'un activateur endogène majeur du facteur profibrosant TGF- (transforming growth factor-b). Son expression, très faible dans le parenchyme sain, augmente significativement après une agression rénale. L'inhibition de ses différents domaines par des anticorps ou peptides spécifiques, le blocage de son expression par des oligonucléotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…It was significantly up-regulated (2-fold) in response to diclofenac treatment and is released early during the acute phase response. Importantly, THBS1 activates transforming growth factor (TGF)-β, a key molecule in the development of liver fibrosis [ 129 131 ] and inflammatory renal diseases [ 132 134 ]. Several studies reported increased expression of THBS1 in hepatic fibrosis and hepatocellular carcinoma [ 130 , 135 , 136 ], and a recent review summarizes the function of THBS1 and its activity via CD47 in inhibiting NO, cGMP, cAMP and VEGF signalling to promote thrombosis and to decrease tissue survival [ 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was significantly up-regulated (2-fold) in response to diclofenac treatment and is released early during the acute phase response. Importantly, THBS1 activates transforming growth factor (TGF)-β, a key molecule in the development of liver fibrosis [ 129 131 ] and inflammatory renal diseases [ 132 134 ]. Several studies reported increased expression of THBS1 in hepatic fibrosis and hepatocellular carcinoma [ 130 , 135 , 136 ], and a recent review summarizes the function of THBS1 and its activity via CD47 in inhibiting NO, cGMP, cAMP and VEGF signalling to promote thrombosis and to decrease tissue survival [ 137 ].…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility, we performed literature analysis of the 28 down-regulated secretory proteins for validated interactions. Literature analysis revealed that among the 28 down-regulated secretory proteins, Pf4 and thrombospondin 1 (THBS1) can bind to heparin 17 , 18 . SPARC, which is among the 28 downregulated secretory proteins, is an acidic protein like heparin 19 .…”
Section: Resultsmentioning
confidence: 99%